Perlindungan Merek UMKM Di Era Digital: Kepastian & Tantangan Penegakan Hukum - Adristy, Baiq Shefania; Disemadi, Hari Sutra; Sudirman, Lu (Jurnal Restorative Justice, 2024)
This research is conducted to examine the problem of legal protection of MSME brands in the digitalization era in the scope of legislation, challenges and law enforcement processes. This research uses normative juridical research and is descriptive qualitative with a statutory approach, concept approach and comparative approach. The results show that first, the laws and regulations that accommodate the protection of MSME brands include Law No.20 of 2016, Law No.20 of 2008, PP No.7 of 2021 and PP No.28 of 2019. The form of MSME brand protection is carried out by constitutive methods and is carried out by means of collective registration, procurement of cooperation, special relief and provision of financing. Unfortunately, in terms of regulation it has weaknesses in the form of potential ownership of the brand not from the original inventor. This is different from the constitutive system in the United States which uses the consideration of use in commerce and intent to use in commerce in determining the rights to the trademark. Second, the challenges of law enforcement of MSME brand protection in the digital era are the lack of public knowledge regarding trademark registration and trademark infringement to the decline in public enthusiasm and awareness in protecting MSME brands. On this basis, DJKI then conducts law enforcement by following up complaints of trademark infringement, optimizing trademark protection programs, conducting socialization and education, holding cooperation to form a special task force. The protection of MSME brands is crucial because it can prevent brand infringement, support the creative industry and maintain brand originality.